Gene therapy for Parkinson's disease: contemporary practice and emerging concepts. (2nd June 2020) - Merola, Aristide; Van Laar, Amber; Lonser, Russell; Bankiewicz, Krzysztof
ABSTRACT: Introduction: Gene therapy is a rapidly evolving technology that has predominantly utilized viral vectors to effectively deliver genetic material inside neurons to modulate the expression of one or more particular genes. Several gene therapy clinical trials have been conducted in Parkinson's disease (PD) by exploring strategies to either restore dopamine synthesis, enhance the production of trophic factors, enhance lysosomal function, or modify the interaction between different functional nodes of the basal ganglia. Areas covered: In this review, the authors sought to discuss contemporary practice, emerging concepts, and unmet needs for the future of gene therapy in PD. Expert opinion: While safety has been demonstrated, clinical trials on gene therapy for PD highlight the need for higher than anticipated volumes of infusion in order to optimize dose and vector coverage. Neurosurgical delivery techniques for gene therapy have rapidly evolved from the use of multiple trans-frontal trajectories to a single parietooccipital shape-conforming infusion. The employment of convection-enhanced delivery with reflux-resistant cannulas has further improved the vector diffusion into the target structures. Future technological developments will reduce the invasiveness and duration of surgery, improve specificity and transduction capacity with novel capsid designs, and implement strategies to control transgene expression.